The Reluctant Assassin: W.A.R.P. #1 - Colfer, Eoin (New York : Hyperion, 2013)
In Victorian London, Albert Garrick, an assassin-for-hire, and his reluctant young apprentice, Riley, are transported via wormhole to modern London, where Riley teams up with a young FBI agent to stop Garrick from returning to his own time and using his newly acquired scientific knowledge and power to change the world forever.
Keywords: Time travel -- Fiction; Assassins -- Fiction; London (England) -- History -- 19th century -- Fiction; Great Britain -- History -- Victoria, 1837-1901 -- Fiction; Science fiction